School Leaders’ Practice of the Ethics of Educational Leadership to Make Decisions - Assiri, Mohammed (Journal of Education in Black Sea Region, 2018)
Abstract This study aimed to investigate the extent to which school leaders practice the ethics of educational leadership to make decisions. A mixed-methods research design was used in this study. The quantitative data of this study were obtained from the participation of 260 teachers, and the qualitative data of this study were collected from nine school leaders. The questionnaire and the semi-structured interview were used to collect the data. The study was conducted during the school year of 2017-2018. The study found that the overall extent to which school leaders practice the ethics of educational leadership to make decisions was classified as “always occurs". The findings showed that there were statistically significant differences between participants with different gender and school levels on the overall and all dimensions of the extent to which school leaders practice the ethics of educational leadership to make decisions, while there were not statistically significant differences between the groups of the participants with different teaching experience. The qualitative findings provided some common factors that influence school leaders’ practice to making ethical decisions. These factors were explained based on two concepts including management knowledge and leadership skills as well as the context of school’s culture.